Identification of chloroplast transit peptides inDunaliella salina and their application for heterologous astaxanthin production - Jv-Liang Dai; Ling Xiao; Yue-Li Yuan; Ming-Hua Liang; Jian-Guo Jiang (Bioresource Technology, 2027)

eIF6 affects the occurrence and development of esophageal cancer - Cong-Gai Huang; Xin Zhou; Ran Huang; Hui-Ling Zhang; Chen-Xi Li; Fei Du; Hong Lei; Qiong Dai; Zhi-Hui Yang (Molecular Biology Reports, 2026)

Microbial kinetics revealed the deterioration mechanism of flavor quality of modified atmosphere packaging Tricholoma matsutake - Ningjing Guo; Ya Dai; Yunkun Ling; Xue Li; Thomas Lettmann; George Owuor; Xiang Li (Postharvest Biology and Technology, 2026)

Effects of endogenous fat content on gel network, physicochemical properties, and flavor of plant-based coconut yogurt: a comparative study with dairy-based counterpart - Xuyan Zong; Xinyu Zhang; Ling Wu; Shujuan Shao; Junya Zhou; Wei Dai; Chunli Liu; Li Li; Guangbin Ye (Food Research International, 2026)

A lyophilized RPA–CRISPR/Cas13d one-pot platform for rapid detection of porcine circovirus type 3 - Li-Na Shao; Zheng-Luo; Bao-Ling Liu; Tong-Xu; Yuan-Meng Wang; Jia-Qi Duan; Lei-Zhao; You-You Li; Yang-Ming Dai; Qin-Rui Jia; Le-Yi Zhang; Ling-Zhu; et al. (Analytica Chimica Acta, 2026)

Mechanisms of growth regulation and environmental effects of ambient nutrients on Vallisneria natans in eutrophic lakes - Weijie Li; Bingbing Liang; Ling Li; Yutai Dai; Jiping Chen; Mengdi Zhao; Hong Shen; Qiang Gao; Xi Yang; Dongqin Wang; Xuwei Deng (Water Research, 2026)

Cadmium induced ferroptosis of TM4 cells through PERK-ATF4-CHOP signaling pathway - Xuan Li; Juan Dai; Jiaoyang Wei; Yan He; Yue Han; Ting Zhou; Rui Li; Ling Zhang; Yuqin Shi (Reproductive Toxicology, 2026)

Decoding genetic basis of nitrogen use efficiency in maize using AI-generated deep phenotypes - Haoyan Yang; Lingju Zeng; Xiangjian Gou; Yang Shao; Xianlong Song; Shuang Zhang; Xiaoyan Qian; Zhenwei Zhang; Xiao Wang; Haitao Li; Bo Peng; Juliet Nkiruka Anyanwu; et al. (Molecular Plant, 2026)

Differential effects of a novel mesoionic insecticide, triflumezopyrim, on Apis mellifera and Apis cerana - Mei-Ling Zhang; Shu-Wei Wang; Wen-Min Li; Sasiprapa Krongdang; Yan-Yan Wu; Ping-Li Dai; Shan-Shan Li; Jing Gao (Journal of Hazardous Materials, 2026)

Boosting aqueous Zn-ion battery performance with Co2+-doped δ-MnO2/Ti3C2Tx cathode through enhanced ion transport and structural stabilization - Shuo Li; Jing Zhu; Longkun Wu; Yasong Han; Ningning Zhao; Bin Li; Shaaban M. Shaaban; Lei Dai; Ling Wang; Zhangxing He (Chemical Engineering Journal, 2026)

Uncovering time-lagged causal mechanisms in hyperthermophilic composting using Peter–Clark momentary conditional independence algorithm - Yanping Zhang; Youzhao Wang; Ling Zhou; Fuxin Yang; Xu Li; Chaoyue Zhao; Shujie Hou; Bingzhen Li; Ziwei Dai; Ziqian Wang; Xinchang Zhou; Qiyu Gong; et al. (Bioresource Technology, 2026)

Pseudostellaria heterophylla Extract Enhances the Immune Responses in Larimichthys crocea Against Pseudomonas plecoglossicida Infection - Kun Huang Han; Zi Min Li; Li Zhou; Dong Ling Zhang; Ying Li; Zhao Han Sun; Jia Chen; Zhi Deng Lin; Yan Bin Dai; Peng Fei Zou (Fishes, 2026)
Visceral white spot disease caused by Pseudomonas plecoglossicida poses a severe threat to large yellow croaker (Larimichthys crocea) aquaculture. This study investigated the immunomodulatory effects and underlying mechanisms of Pseudostellaria heterophylla extract against P. plecoglossicida infection in L. crocea. Fish were fed a basal diet supplemented with 1% P. heterophylla extract for 30, 45, and 60 days, followed by intraperitoneal injection with 200 μL P. plecoglossicida (1 × 104 CFU/mL). When the control group reached about 50% mortality, transcriptome sequencing of head kidney tissues was performed on the 45 and 60 days post-feeding of the treatment groups to analyze gene expression changes following bacterial infection. Survival rates of the treatment groups were 33.33%, 13.33%, and 20% higher than those of the control group at 30, 45, and 60 days post-feeding, respectively. Transcriptomic analysis revealed time-dependent transcriptional responses: in one group, 45 days post-feeding, 10 differentially expressed genes (DEGs) were identified (2 up-regulated and 8 down-regulated), whereas in another group, 60 days post-feeding, 893 DEGs were detected (417 up-regulated and 476 down-regulated). Functional enrichment analysis (GO, KEGG, and GSEA) demonstrated that DEGs were significantly enriched in immune-related pathways, including Toll-like receptor signaling, chemokine activity, Th1 and Th2 cell differentiation, hematopoietic cell lineage, and cytokine–cytokine receptor interaction. Key immune genes, including chemokines, Toll-like receptors, and T cell regulators, were significantly up-regulated. These findings indicate that P. heterophylla extract enhances both the specific and non-specific immune capabilities of L. crocea in a time-dependent manner, with prolonged supplementation eliciting more robust transcriptional activation of immune defense pathways. This study provides a scientific foundation for developing immunological prevention strategies against P. plecoglossicida infection in aquaculture.

Regional immunity in the respiratory tract: challenges and opportunities - Shuo Wang; Si Chen; Lianpan Dai; Fengqi Li; Hui Li; Kefang Liu; Xiangzhi Meng; Jian Wang; Hua Yue; Airu Zhu; Bin Cao; Ling Chen; et al. (Science Bulletin, 2026)

A novel phytoformula targeting lipid peroxidation inhibition attenuates UV-induced skin photoaging - Ling-Ping Wu; Wei Chen; Qian-Pei Lin; Shi-Yun Feng; Jin Dai; Qiong-Yi Zhang; Wen-Yi Chen; Hiroshi Kurihara; Xiao-Min Li; Shu-Hua Ouyang; Yi-Fang Li; Rong-Rong He (PharmaNutrition, 2026)

Janus SiS2/SeWS heterojunction as a high-performance direct Z-scheme photocatalyst for spontaneous overall water splitting - Qiyun Wang; Zhenwu Jin; Shuqi Dai; Yifan Yang; Lu Liu; Yi Li; Ling-Ling Wang; Liang Xu (Fuel, 2026)

Secondhand and thirdhand smoke exposure and the risk of liver cancer: a prospective cohort study of 315,833 Chinese never smokers - Zhi Li; Ling-Xiang Xu; Chun-Rui Wang; Zhang-You Guo; Chen-Wei Tang; Xin Dai; Guo-Chao Zhong (Environmental Pollution, 2026)

Structural and functional characterization of pectic polysaccharide fractions isolated from Choerospondias axillaris flesh - Qian Li; Rui Kang; Hongyi Lin; Yuanhang Wan; Taotao Dai; Panting Tian; Huashan Ling; David Julian McClements; Peiyi Shen; Jun Chen (Food Chemistry, 2026)

Preparation of cancer cell membrane-coated Gambogic acid-loaded pH-sensitive liposomes to enhance targeted anti-hepatocellular carcinoma effect - Yi-Feng Zhang; Kun Chen; Yu-Qing Zhu; Lin Liu; Xiang-Tao Kong; Yan Dai; Xiu-Juan Fu; Ya-Ling Li; Ming-Hua Liu; Dan Zhang (Drug Delivery and Translational Research, 2026)

Dual regulation of surface termination and interlayer spacing of MXene for high-performance vanadium redox flow batteries - Tianxing Yuan; Xingrong Chen; Yanqin Zhao; Yingqiao Jiang; Bin Li; Ningning Zhao; Jing Zhu; Lei Dai; Ling Wang; Zhangxing He (Chemical Engineering Journal, 2026)

Comparative analysis of PRV-induced neuropathology and blood–brain barrier disruption identifies C57BL/6 as the most susceptible mouse model - Tong Xu; Hanyu Li; Baoling Liu; Lei Zhao; Yangming Dai; Xin Wu; Siyuan Lai; Jian-Bo Huang; Ling Zhu; Zhi-Wen Xu (Veterinary Microbiology, 2026)

Differences in ozone formation among urban, suburban, and rural areas: A case study in a typical industrial city in the North China plain - Peng Liu; Kun Zhang; Jin Xue; Jingwen Dai; Yangjun Wang; Ling Huang; Li Li (Environmental Pollution, 2026)

Changes in Soil Phosphorus Fractions Across Soil Depths Under Continuous Wheat-Faba Bean Intercropping - Wenlian Bai; Rong Dai; Ling Qian; Weiwu Changjin; Li Tang; Yi Zheng; Jingxiu Xiao (Journal of Soil Science and Plant Nutrition, 2026)

Variations in hydrochemical characteristics and their controlling factors among different types of lakes in the northeastern region of the Qinghai-Xizang Plateau - Jiping Chen; Ling Li; Weijie Li; Bingbing Liang; Yu Lin; Yutai Dai; Mengdi Zhao; Hong Shen; Xi Yang; Qiang Gao; Xuwei Deng (Environmental Monitoring and Assessment, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Divergent roles of three glycerol-3-phosphate dehydrogenase isoforms in glycerol and lipid metabolism of Dunaliella salina and their implications for biodiesel production - Jv-Liang Dai; Ling Xiao; Yue-Li Yuan; Ming-Hua Liang; Jian-Guo Jiang (Bioresource Technology, 2026)

Microplastics and nanoplastics, emerging pollutants, increased the risk of pulmonary fibrosis in vivo and in vitro: A comparative evaluation of their potential toxicity effects with different polymers and size - Jia-Yi Dou; Sen Liu; Chen-Yu Wang; Xu Dai; Li-Hua Lian; Zhen-Yu Cui; Ji-Xing Nan; Yan-Ling Wu (Toxicology, 2026)

From metamorphic to magmatic fluids: Decoding of Yanshanian Au mineralization process in the Wangu gold deposit, southern China - Yong-shun Li; Yong-jun Shao; Zhong-fa Liu; Ke Chen; Xue-ling Dai; Ming-hui Chen; Ming-peng He; Qing Gou (Journal of Asian Earth Sciences, 2026)

Smartphone-integrated luminescent Europium-organic framework sensor for on-off ratiometric identification of levofloxacin in water and milk samples - Lei-Ming Dai; Ling Li; Sheng-Yong You; Li Zhang; Mei-Feng Wu; Ji-Yong Zou (Analytica Chimica Acta, 2026)

Amino-functionalized electrospinning separator tailors desolvation kinetics and Zn2+ transport for high-performance aqueous zinc-ion batteries - Zhuoqun Liu; Luxin Yu; Zhenying Zhang; Yang Feng; Bin Li; Yingqiao Jiang; Ningning Zhao; Jing Zhu; Lei Dai; Ling Wang; Zhangxing He (Chemical Engineering Journal, 2025)

Different Intensities of Exercise Affect the Prognosis of Ventricular Aneurysm in Mice by Regulating the Progression of Cardiac Fibrosis - Rui-Qiang Qi; Juan Song; Hong-Bin Ma; Mei-Ling Nie; Liu-Hang Su; Cui-Lian Dai; Fa-Guang Zhou; Sui-Ji Li (Cardiovascular Toxicology, 2025)

Application of magnetic amplitude inversion in the identification of igneous rocks in superimposed basins: a case study in Qikou depression - Shu-ling Li; Jirigalatu; Xue-ping Dai (Applied Geophysics, 2025)

New natural products from Rhododendron ciliicalyx subsp. Lyi - Chun-Lin Guo; Si-Xuan Liu; Lu Zhang; Ling Li; Yong-Fu Lu; Si-Yang Dai; Chang Li; Yue-Hu Pei (Phytochemistry Letters, 2025)

Interface modification of fluopyram-loaded microcapsules using Fe3+/lignosulfonate via coordination and electrostatic interactions to improve nematicide rhizosphere utilization - Haichao Cao; Yanhou Zhao; Jiangzhou Li; Kuai Dai; Lijun Jiang; Wenzheng Ling; Wei Mu; Chao Feng; Dan Chen; Jinguang Yang (Chemical Engineering Journal, 2025)

Anaerobic Digestion Enhances the Comprehensive Utilization of Shaddock Peel: Methane Production, Biochar Preparation, and CO2 Capture - Chengcheng Cao; Ru Li; Huantao Dai; Yan Zhao; Ling Sun; Xinheng Zhuang; Xueyang Zhang (Water, Air, & Soil Pollution, 2025)

Cadmium induces autophagy via IRE1 signaling pathway activated by Ca2 + in GC-2spd cells - Yue Han; Juan Dai; Jinxin Cheng; Yan He; Chengkun Zhao; Rui Li; Yaqin Zhang; Ling Zhang; Ting Zhou; Yuqin Shi (Reproductive Toxicology, 2025)

Milk vetch (Astragalus sinicus L.) affects microbial-driven rice straw decomposition in multiple stages - Xinling Ma; Qingjun Dai; Wenjing Qin; Jia Liu; Xiaoli Liu; Ling Chen; Jianbo Fan; Meng Wu; Daming Li; Ming Liu (Plant and Soil, 2025)

Chondroitin sulfate alleviates leaf senescence of Chinese flowering cabbage by modulating homeostasis of ROS and chlorophyll catabolism during storage - Pengfei Du; Yaqi Li; Yulong Chen; Hua Huang; Fanwei Dai; Jianye Chen; Mingqiang Ye; Feiping Chen; Yingwei Qi; Zheng Luo; Ling Wang (Postharvest Biology and Technology, 2025)

PRDX1 affects acrylamide-induced neural damage through the PTEN/AKT signaling pathway - Dong-Xue Fu; Ya-Ting Lei; Hai-Bo Guo; Ting Chen; Xiang-Ying Gao; Xiao-Li Wang; Xiang Huang; Ling-Ling Song; Sheng-Yuan Wang; Qin-Xue Dai (NeuroToxicology, 2025)

Accelerated detection of carbapenem resistance in Klebsiella pneumoniae via single-cell Raman spectroscopy - Jia-Cheng Ding; Li-Ting Dai; Jia-Xin Tang; Hui-Min Zhang; Le-Le Zhai; Chuang-Ye Cai; Zhi-Rou Xiao; Zhe-Mei Chen; Jia-Hui Ling; Meng-Xue Zou; Xi-Wu Cao; Li-Juan Lin; et al. (World Journal of Microbiology and Biotechnology, 2025)

Short-term effects of sulfate on ammonia-oxidizing microorganisms in freshwater aquaculture pond sediments - Lili Dai; Liqin Yu; Liang Peng; Ling Tao; Liuliu Hao; Hui Zhang; Gu Li (Journal of Soils and Sediments, 2025)

Development of electrochemical NH3 sensors with large sensitivity depending on the superposition enhancement effect of sensing electrodes - Xiaodi Xu; Weiwei Meng; Fanbo Kong; Bo Yan; Shijie Zheng; Xu Li; Jing Zhu; Zhangxing He; Yuehua Li; Wei Meng; Lei Dai; Ling Wang (Chemical Engineering Journal, 2025)

The Current State and Future Outlook of PET Tracers for AMPA Receptors - Ling Li; Shenglin Wen; Ji Dai (Neuroscience Bulletin, 2025)

Groundwater environmental effects risk evaluation in mountain tunnel construction: A dynamic decision support system based on fuzzy two-dimensional cloud probability model - Huaiyuan Sun; Ling Le; Yiming Dai; Yi Rui; Hehua Zhu; Xiaojun Li; Xuhui Li; Guangwen Xue (Tunnelling and Underground Space Technology, 2025)

Mechanism of crustal deformation around the Lajishan-Jishishan Tectonic Belt, NE Tibet, and implications for occurrence of the 2023 Jishishan MS 6.2 earthquake - Haoqing Liu; Weijun Gan; Yujiang Li; Zhangjun Li; Lishen Liu; Ling Zhang; Shiming Liang; Keliang Zhang; Yanchuan Li; Chenglong Dai (Journal of Asian Earth Sciences, 2025)

Characteristics of thermal comfort for the elderly in urban parks during autumn: a case study in cold regions - Hu Luyao; Lu Ling; Li Xinkai; Dai Junfeng (Theoretical and Applied Climatology, 2025)

Salinity affects C/N ratio through differential responses of carbon and nitrogen metabolism in mangrove Avicennia marina leaves revealed by combined analysis of transcriptome and metabolome - Jing Li; Ling-Yu Song; Ze-Jun Guo; Chao-Qun Xu; Lu-Dan Zhang; Ji-Cheng Wang; Han-Chen Tang; Ming-Jin Dai; Xue-Yi Zhu; Hai-Lei Zheng (Plant and Soil, 2025)

Design, synthesis and herbicidal activity of novel cyclohexanedione derivations containing pyrazole and pyridine groups as potential HPPD inhibitors - Shuai-Tao Hou; Ling Han; Wen-Rui Li; Guang-Yu Dai; Yu Liu; Ai-Min Lu; Chun-Long Yang; Min Chen (Molecular Diversity, 2025)

Protective effect of Apelin-13 on oxygen and glucose deprivation induced-damage in retinal ganglion cells cultured in vitro - Li Dai; Linlin Luo; Ya Zhang; Min Fu; Ling Yu (Journal of Molecular Histology, 2025)

Rice-crayfish farming enhances soil organic carbon by increasing labile organic carbon and altering microbial functions - Liang Peng; Liuliu Hao; Lili Dai; Ling Tao; Hui Zhang; Gu Li; Jianqiang Zhu (Applied Soil Ecology, 2025)

Recent progress and perspectives of single-atom catalysts with framework architecture for zinc-air battery cathodes - Zekun Zhang; Jia Dong; Chunting Huang; Kexin Wan; Zemin Feng; Bin Li; Ningning Zhao; Lei Dai; Ling Wang; Zhangxing He (Chemical Engineering Journal, 2025)

RO4929097 inhibits NICD3 to alleviate pulmonary hypertension via blocking Notch3/HIF-2α/FoxM1 signaling pathway - Hao Zhu; Cheng Li; Fang Hu; Lifu Wu; Ling Wu; Meihua Zhou; Wei Liu; Aiguo Dai (In Vitro Cellular & Developmental Biology - Animal, 2025)

Conjugated diamine cation based halide perovskitoid enables robust stability and high photodetector performance - Xin Yang; Xu-Dong Wang; Wen-Guang Li; Yu-Hua Huang; Ling-Bin Wang; Jia-Min Liu; Long Jiang; Dai-Bin Kuang (Science Bulletin, 2024)

circFKBP8(5S,6)-encoded protein as a novel endogenous regulator in major depressive disorder by inhibiting glucocorticoid receptor nucleus translocation - Jiao Jiao; Dandan Xu; Yan Kong; Yujia Cao; Liyuan Wang; Yuan Hong; Ling Li; Chenyu Gao; Jing Liu; Gaojia Zhang; Jiangning Zhou; Ji Dai; et al. (Science Bulletin, 2024)

ent-Kaurane diterpenoids from Isodon henryi and their anti-inflammatory activities - Yi-xiao Li; Jun Chi; Ling-xia Zhang; Fang Wang; Wei-jin Zhang; Zhi-min Wang; Li-ping Dai (Phytochemistry, 2024)

Calcium regulates the physiological and molecular responses of Morus alba roots to cadmium stress - Ming-Jin Dai; Lu-Dan Zhang; Jing Li; Chun-Quan Zhu; Ling-Yu Song; He-Zi Huang; Chao-Qun Xu; Qing-Hua Li; Lin Chen; Chen-Kai Jiang; Hong-Ling Lu; Qiu-Tong Ling; et al. (Journal of Hazardous Materials, 2024)

Abrupt topographic descent at the eastern end of the Himalayan orogen: Insights from geodetic analyses - Shiming Liang; Ling Zhang; Weijun Gan; Keliang Zhang; Genru Xiao; Zhangjun Li; Chenglong Dai; Haoqing Liu; Demin Zhou (Journal of Asian Earth Sciences, 2024)

Reduction of nutrient fluxes across the sediment–water interface and nutrient accumulation in lotus-fish co-culture aquaculture ponds - Zhen Yang; Meng Sun; Liang Peng; Lili Dai; Jianqiang Zhu; Gu Li; Ling Tao; Hui Zhang (Aquaculture International, 2024)

Zinc-tin binary alloy interphase for zinc metal batteries - Xinyan Zhu; Weisong Zhang; Ziyu Peng; Liang Pan; Bin Li; Zekun Zhang; Jing Zhu; Wei Meng; Lei Dai; Ling Wang; Zhangxing He (Chemical Engineering Journal, 2024)

Endoplasmic reticulum stress response modulator OsbZIP39 regulates cadmium accumulation via activating the expression of defensin-like gene OsCAL2 in rice - Jian Li; Ling-Yan Wang; Huan-Chao Huang; Wu Yang; Guang-Yi Dai; Zhi-Qiang Fang; Jun-Liang Zhao; Kuai-Fei Xia; Xuan Zeng; Meng-Ling He; Nan Yao; Ming-Yong Zhang (Journal of Hazardous Materials, 2024)

Thyroid and parathyroid function disorders induced by short-term exposure of microplastics and nanoplastics: Exploration of toxic mechanisms and early warning biomarkers - Jinpeng Zhang; Ling Liu; Xiaowei Dai; Bo Li; Shaoxuan Zhang; Yong Yu (Journal of Hazardous Materials, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Toward a solid microneedle patch for rapid and enhanced local analgesic action - Yue Liu; Ze Qiang Zhao; Ling Liang; Li Yue Jing; Jianhao Wang; Yun Dai; Bo Zhi Chen; Xin Dong Guo (Drug Delivery and Translational Research, 2024)

ZnMo-MOF as anti-CO hydrogen electrocatalyst enhance microbial electrosynthesis for CO/CO2 conversion - Yu Chen; Yuhang Chen; David Zixiang Dai; Xiang Ling Li; Tianshun Song; Jingjing Xie (Chemosphere, 2024)

Genome-wide analysis of in vivo-evolved Candida auris reveals multidrug-resistance mechanisms - Xin-Fei Chen; Han Zhang; Ling-Li Liu; Li-Na Guo; Wen-Jing Liu; Ya-Li Liu; Ding-Ding Li; Ying Zhao; Ren-Yuan Zhu; Yi Li; Rong-Chen Dai; Shu-Ying Yu; et al. (Mycopathologia, 2024)

Effects of the combined use of kaolinite and dolomite as catalysts for the heavy oil oxidation - Yanqiu Dai; Xianghui Zhang; Runlin Pu; Wei Hu; Ling Wang; Huan Yang; Wenlin Yang; Qin Liu; Ruyan Wang; Zhongquan Li; Qian Feng (Applied Clay Science, 2024)

Identification of volatile compounds and their bioactivities from unpolar fraction of Alpinia oxyphylla Miq. and mining key genes of nootkatone biosynthesis - Fapetu Kemi Busayo; Jin-Ling Yang; Xu-Po Ding; Ya-Li Wang; Cui-Juan Gai; Fei Wu; Hao-Fu Dai; Wen-Li Mei; Hui-Qin Chen (Natural Product Research, 2024)

Micro-aeration and low influent C/N are key environmental factors for achieving ANAMMOX in livestock farming wastewater treatment plants - Yuxin Li; Zhenzhong Pan; Jingsong Liao; Ruizhi Dai; Jih-Gaw Lin; Jiayin Ling; Yanbin Xu (Water Research, 2024)

Cadmium disrupts spermatogenic cell cycle via piRNA-DQ717867/p53 pathway - Jiaoyang Wei; Juan Dai; Xiaofan Shi; Ruixue Zhao; Guoqing Fu; Rui Li; Chao Xia; Ling Zhang; Ting Zhou; Huaiji Wang; Yuqin Shi (Reproductive Toxicology, 2024)

Dual effect of organic/inorganic artificial protective layer to construct high-performance zinc metal anode - Yingxiao Du; Ruotong Li; Tingting Wang; Ziyi Feng; Han Dong; Fangfang Fan; Dezhao Deng; Jing Zhu; Yongguang Liu; Lei Dai; Ling Wang; Zhangxing He (Chemical Engineering Journal, 2024)

Advances in Atmospheric Radiation: Theories, Models, and Their Applications. Part II: Radiative Transfer Models and Related Applications - Hua Zhang; Feng Zhang; Lei Liu; Yuzhi Liu; Husi Letu; Yuanjian Yang; Zhengqiang Li; Kun Wu; Shuai Hu; Ming Li; Tie Dai; Fei Wang; et al. (Journal of Meteorological Research, 2024)

Pigmentiphaga kullae CHJ604 improved the growth of tobacco by degrading allelochemicals and xenobiotics in continuous cropping obstacles - Jia-Xi Xiong; Ling-Shan Du; Na-Na Li; Xiu-Ting Wu; Yang Xiang; Sha Li; Lei Zou; Dongqi Liu; Duo Huang; Ze Feng Xie; Ying Wang; Jinhua Li; et al. (Journal of Hazardous Materials, 2024)

Low phosphorus increases hepatic lipid deposition, oxidative stress and inflammatory response via Acetyl-CoA carboxylase-dependent manner in zebrafish liver cells - Jibin Lin; Jilei Zhang; Weiwei Dai; Xiao Li; Mohamed Mohsen; Xueshan Li; Kangle Lu; Kai Song; Ling Wang; Chunxiao Zhang (Fish & Shellfish Immunology, 2024)

Analysis of resistance risk and mechanism of the 14α-demethylation inhibitor ipconazole in Fusarium pseudograminearum - Guixiang Li; Ling Zhang; Yiwen Li; Xiong Li; Xuheng Gao; Tan Dai; Jianqiang Miao; Xili Liu (Pesticide Biochemistry and Physiology, 2024)

Dual-specificity phosphatase 1 inhibits Singapore grouper iridovirus replication via regulating apoptosis in Epinephelus coioides - Jia-Yang He; Yi-Jie Cai; Yong-Xuan Li; Wei Huang; Yue Zhang; Ke-Jian Liu; Zhuo Sun; Li-Ling Dai; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

A Systematic Review of in Vivo Anterior Cruciate Ligament Loading During Static, Slow-Speed and Athletic Tasks - Ling Li; Yu Song; Boyi Dai (Journal of Science in Sport and Exercise, 2024)

Laccase-evoked removal of antibiotics: Reaction kinetics, conversion mechanisms, and ecotoxicity assessment - Kai Sun; Mei-Hua Chen; Xue-Min Qi; Dan Hong; Ling-Zhi Dai; Shun-Yao Li; Yi-Chen Lu; Han-Qing Yu (Critical Reviews in Environmental Science and Technology, 2024)

Two new anthraquinone derivatives from Saprosma crassipes H. S. Lo - Xin-Shu Ji; De-Cai Dai; Yi-Tong Wang; Jing-Yi Cui; Hai-Xiang Li; Xin-Ming Song; Ji-Ling Yi; Xue-Ming Zhou (Natural Product Research, 2024)

Transcriptome analysis of flower colour reveals the correlation between SNP and differential expression genes in Phalaenopsis - Yu Ding; Ma-Yin Wang; Ding-Hai Yang; Dai-Cheng Hao; Wei-Shi Li; Peng Ling; Shang-Qian Xie (Genes & Genomics, 2023)

Advances in research of ursolic acid and its derivatives as potential drug candidates against various types of lung cancers - Li Song; Ling Dai; Yan Tan; Kailin Jiang; Xueni Wei; Yufei Hu; Yalin Hu; Jieying Lin; Xu Yao; Pengbing Mi; Xing Zheng (Medicinal Chemistry Research, 2023)

Test of the colonization ability of the invasive alien plant Flaveria bidentis (Asteraceae) in southern China - Li Xin-Chen; Chen Xi; Dong Xue-jing; Wang Lai-Le; Yi-chen Li; Shi Zhi-Hua; Song Xiao-ling; Qiang Sheng; Dai Wei-min; Wei-Min Dai (Biological Invasions, 2023)

Functional-structural decoupling in visual network is associated with cognitive decline in patients with type 2 diabetes mellitus: evidence from a multimodal MRI analysis - Min-Hua Ni; Ying Yu; Yang Yang; Ze-Yang Li; Teng Ma; Hao Xie; Si-Ning Li; Pan Dai; Xin-Yu Cao; Yan-Yan Cui; Jun-Ling Zhu; Guang-Bin Cui; et al. (Brain Imaging and Behavior, 2023)

Inventory of cadmium-transporter genes in the root of mangrove plant Avicennia marina under cadmium stress - Lu-Dan Zhang; Ling-Yu Song; Ming-Jin Dai; Jin-Yu Liu; Jing Li; Chao-Qun Xu; Ze-Jun Guo; Shi-Wei Song; Jing-Wen Liu; Xue-Yi Zhu; Hai-Lei Zheng (Journal of Hazardous Materials, 2023)

Loss of Atg5 in Sertoli cells enhances the susceptibility of cadmium-impaired testicular spermatogenesis in mice - Yong-Wei Xiong; Dai-Xin Li; Zheng-Jia Ling; Lu-Lu Tan; Yu-Feng Zhang; Jin Zhang; Hao Li; Wei Chang; Hua-Long Zhu; Jun Zhang; Lan Gao; De-Xiang Xu; et al. (Food and Chemical Toxicology, 2023)

Cytotoxic steroids from the stems of Strophanthus divaricatus - Hong-Ling Ran; Sheng-Zhuo Huang; Hao Wang; Li Yang; Cui-Juan Gai; Rui-Jun Duan; Hao-Fu Dai; Ya-Li Guan; Wen-Li Mei (Phytochemistry, 2023)

Screening, structural characterization and anti-adipogenesis effect of a water-soluble polysaccharide from Lycium barbarum L. by an activity-oriented approach - Han Wang; Yunchun Li; Yunyun Dai; Ling Ma; Duolong Di; Jianfei Liu (Food Bioscience, 2023)

Retraction Note: Ergosterol Attenuates Isoproterenol-Induced Myocardial Cardiotoxicity - Qifei Xie; Suiji Li; Yun Gao; Ling Jin; Cuilian Dai; Juan Song (Cardiovascular Toxicology, 2023)

The Synergistic Activity and Interaction Mechanism of Linoleic Acid and a Bioactive Pentapeptide (Tyr-Val-Pro-His-Trp) from Walnut Meal in the Treatment of Alzheimer’s Disease - Zi-Chun Wang; Yu-Xi Ling; Ya-Xin Liang; Zi-Qi Li; Jie Dai; Di-Feng Ren (International Journal of Peptide Research and Therapeutics, 2023)

Monitoring black tea fermentation quality by intelligent sensors: Comparison of image, e-nose and data fusion - Qiaoyi Zhou; Zhenhua Dai; Feihu Song; Zhenfeng Li; Chunfang Song; Caijin Ling (Food Bioscience, 2023)

Investigation of insecticidal activity of two Rhododendron species on stored-product insects - Yu-Li Sang; Lu Dai; Pei Wang; Li-Jiang Chen; Mei-Ling Jiao; Jing-Yu Liu; Nai-Zhi Zhang; Guang-Wen Fan; Yan-Jun Hao; Xiu-Lan Wang (Journal of Plant Diseases and Protection, 2023)

Changes in the Microbiota and their Roles in Patients with Type 2 Diabetes Mellitus - Qiao-ling He; Hui-chao Wang; Yu-ke Ma; Rui-lin Yang; Zhi-feng Dai; Jing-nan Yang; Yao Xu; Dan-dan Wei; Li-ping Zhu; Xu-hong Lin (Current Microbiology, 2023)

High-activity and stability graphite felt supported by Fe, N, S co-doped carbon nanofibers derived from bimetal-organic framework for vanadium redox flow battery - Qingchun Jiang; Yujie Ren; Yujie Yang; Honghao Liu; Ling Wang; Jin Li; Lei Dai; Zhangxing He (Chemical Engineering Journal, 2023)

A new phragmalin-type limonoid from the roots of Trichilia sinensis - Shou-Bai Liu; Jin-Ling Yang; Hui-Qin Chen; Cheng-min Yang; Hao Wang; Cai-Hong Cai; Jing-Zhe Yuan; Wen-Li Mei; Hao-Fu Dai (Phytochemistry Letters, 2023)

Catalytic capacity evolution of montmorillonite in in-situ combustion of heavy oil - Xianghui Zhang; Junjie Wang; Ling Wang; Zhongquan Li; Wei Hu; Yanqiu Dai; Yuanyu Kou; Shengjun Lei; Qian Li; Wen Zhang; Hongkui Li; Ruyan Wang; et al. (Fuel, 2023)

Origin of natural gas within the deep-sea uncompacted sediments of the Shenhu area, northern South China Sea: Geochemical and methanogenic cultivation results - Hongfei Lai; Yinan Deng; Lu Yang; Jinqiang Liang; Lirong Dai; Ling Li; Yunxin Fang; Laiyan Liu; Zenggui Kuang (Marine and Petroleum Geology, 2023)

Structural deformation, metallogenic epoch and genetic mechanism of the Woxi Au-Sb-W deposit, Western Hunan Province, South China - Bin Li; Deru Xu; Daoyuan Bai; Guoxiang Chi; Junfeng Dai; Cheng Gao; Teng Deng; Shaohao Zou; Wen Ma; Guojian Wang; Yuexin Ling; Guangqian Zeng; et al. (Science China Earth Sciences, 2022)

Contamination of 16 priority polycyclic aromatic hydrocarbons (PAHs) in urban source water at the tidal reach of the Yangtze River - Qi Dai; Yanyan Wang; Ling Chen; Pan Li; Shengji Xia; Qinghui Huang (Environmental Science and Pollution Research, 2022)

Efficient de novo assembly and modification of large DNA fragments - Shuangying Jiang; Yuanwei Tang; Liang Xiang; Xinlu Zhu; Zelin Cai; Ling Li; Yingxi Chen; Peishuang Chen; Yuge Feng; Xin Lin; Guoqiang Li; Jafar Sharif; et al. (Science China Life Sciences, 2022)

Three-Dimensional DC Anisotropic Resistivity Modeling Using a Method in the Mixed Space–Wavenumber Domain - Jiaxuan Ling; Shikun Dai; Yinming Zhou; Qingrui Chen; Ying Zhang; Kun Li (Pure and Applied Geophysics, 2022)

Identification of fruit firmness QTL ff2.1 by SLAF-BSA and QTL mapping in melon - Dongyang Dai; Shuang Zeng; Ling Wang; Junfeng Li; Peng Ji; Huiying Liu; Yunyan Sheng (Euphytica, 2022)

Functional Mechanism of Antimicrobial Peptide Bomidin and Its Safety for Macrobrachium rosenbergii - Miao Zhang; Youli Yu; Lele Lian; Wanjun Li; Jianluan Ren; Ying Liang; Feng Xue; Fang Tang; Xiaohua Zhu; Jianqun Ling; Jianjun Dai (Probiotics and Antimicrobial Proteins, 2022)

Technical methodologies for the assessment of the impacts of reclamation projects on marine ecology - Yurong Ouyang; Lin Wu; Juanjuan Dai; Yaojian Wu; Ling Cai; Qingsheng Li; Jianwei Wu; Shang Jiang (Environmental Science and Pollution Research, 2022)

Numerical modeling of 3D DC resistivity method in the mixed space-wavenumber domain - Shi-Kun Dai; Jia-Xuan Ling; Qing-Rui Chen; Kun Li; Qian-Jiang Zhang; Dong-Dong Zhao; Ying Zhang (Applied Geophysics, 2021)

A new ent -kaurane diterpene from Isodon henryi - Xue Jiang; Ling-Xia Zhang; Qing-Mei Feng; Hong Wu; Ya-Lin Liu; De-Qin Wang; Li-Ping Dai; Zhi-Min Wang (Natural Product Research, 2021)

Resolvin D1 Attenuates Innate Immune Reactions in Experimental Subarachnoid Hemorrhage Rat Model - Guang-Jie Liu; Tao Tao; Xiang-Sheng Zhang; Yue Lu; Ling-Yun Wu; Yong-Yue Gao; Han Wang; Hai-Bin Dai; Yan Zhou; Zong Zhuang; Chun-Hua Hang; Wei Li (Molecular Neurobiology, 2021)

Early-Life Multiple Sevoflurane Exposures Alleviate Long-term Anxiety-Like Behaviors in Mice via the proBDNF/ERK Pathway - Ru-Yi Luo; Cong Luo; Feng Zhong; Wei-Yun Shen; Hui Li; Yan-Ling Zhang; Ru-Ping Dai (Molecular Neurobiology, 2021)

Correction to: Involvement of proBDNF in Monocytes/Macrophages with Gastrointestinal Disorders in Depressive Mice - Yun-Qing Yu; Yan-Ling Zhang; Zhe Wang; Yu Liu; Hui Li; Chang-Qi Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2020)

Involvement of proBDNF in Monocytes/Macrophages with Gastrointestinal Disorders in Depressive Mice - Yun-Qing Yu; Yan-Ling Zhang; Zhe Wang; Yu Liu; Hui Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2020)

RETRACTED ARTICLE: Ergosterol Attenuates Isoproterenol-Induced Myocardial Cardiotoxicity - Qifei Xie; Suiji Li; Yun Gao; Ling Jin; Cuilian Dai; Juan Song (Cardiovascular Toxicology, 2020)

Neonatal Exposure to Anesthesia Leads to Cognitive Deficits in Old Age: Prevention with Intranasal Administration of Insulin in Mice - Chun-Ling Dai; Hengchang Li; Xin Hu; Jin Zhang; Fei Liu; Khalid Iqbal; Cheng-Xin Gong (Neurotoxicity Research, 2020)

Acanthophoraine A, a new pyrrolidine alkaloid from the red alga Acanthophora spicifera - Jia-Li Lin; Yong-Qian Liang; Xiao-Jian Liao; Jian-Ting Yang; Dai-Chun Li; Yu-Ling Huang; Zhi-Hui Jiang; Shi-Hai Xu; Bing-Xin Zhao (Natural Product Research, 2020)

Epidemiology and HBGA-susceptibility investigation of a G9P[8] rotavirus outbreak in a school in Lechang, China - Lun-Ai Guo; Meng Zhang; Yu-zhen Hou; Haitao Hu; Ling Fang; Ming Tan; Qiong Huang; Hui Li; Li-Mei Sun; Xi Jiang; Wen-Fang Tan; Shixing Tang; et al. (Archives of Virology, 2020)

Proteomic discovery of H2O2 response in roots and functional characterization of PutGLP gene from alkaligrass - Juanjuan Yu; Yongxue Zhang; Junming Liu; Lin Wang; Panpan Liu; Zepeng Yin; Siyi Guo; Jun Ma; Zhuang Lu; Tai Wang; Yimin She; Yuchen Miao; et al. (Planta, 2018)

Evaluating tacrolimus pharmacokinetic models in adult renal transplant recipients with different CYP3A5 genotypes - Can Hu; Wen-jun Yin; Dai-yang Li; Jun-jie Ding; Ling-yun Zhou; Jiang-lin Wang; Rong-rong Ma; Kun Liu; Ge Zhou; Xiao-cong Zuo (European Journal of Clinical Pharmacology, 2018)

Late Cretaceous basalts and rhyolites from Shimaoshan Group in eastern Fujian Province, SE China: age, petrogenesis, and tectonic implications - Xi-Yao Li; San-Zhong Li; Yan-Hui Suo; Li-Ming Dai; Ling-Li Guo; Feng-Jian Ge; Pei-Jun Lin (International Geology Review, 2018)

Isolation and purification of diterpenoids from the aerial parts of Isodon excisoides target-guided by UPLC-LTQ-Orbitrap-MS - Li-Ping Dai; Ling-Xia Zhang; Ya-Lin Liu; Hong Wu; Rui-Xin Liu; Meng Zhao; Shuang-Shuang Tian; Xue Jiang; Sui-Qing Chen (Natural Product Research, 2018)

Fast 3D forward modeling of the magnetic field and gradient tensor on an undulated surface - Kun Li; Long-Wei Chen; Qing-Rui Chen; Shi-Kun Dai; Qian-Jiang Zhang; Dong-Dong Zhao; Jia-Xuan Ling (Applied Geophysics, 2018)

Construction and characterization of a bacterial artificial chromosome library for Camellia sinensis - Yuling Tai; Hao Wang; Chaoling Wei; Ling Su; Min Li; Liqun Wang; Zhaozhao Dai; Lingyun Shao; Jiayue Jiang; Meizhong Luo; Hua Yang; Weiwei Deng; et al. (Tree Genetics & Genomes, 2017)

Association of folate metabolism gene polymorphisms and haplotype combination with pulmonary embolism risk in Chinese Han population - Xin Li; Ling Weng; Baihe Han; Yingnan Dai; Li Cha; Shujun Yan; Enze Jin (Mammalian Genome, 2017)

Complete genomic characterization of two European-genotype porcine reproductive and respiratory syndrome virus isolates in Fujian province of China - Jian-Kui Liu; Chun-Hua Wei; AI-Ling Dai; Ke-Wei Fan; Bing-Hui Yang; Chun-Fang Huang; Xiao-Hua Li; Xiao-Yan Yang; Man-Lin Luo (Archives of Virology, 2017)

Cytotoxic monoterpenoid indole alkaloids isolated from the barks of Voacanga africana Staph. - Hong-Mei Chen; Yu-Ting Yang; Hong-Xiang Li; Zhi-Xing Cao; Xiao-Mei Dan; Ling Mei; Da-Le Guo; Chuan-Xia Song; Yu Dai; Jia Hu; Yun Deng (Natural Product Research, 2016)

High Serum MiR-130a Levels Are Associated with Severe Perihematomal Edema and Predict Adverse Outcome in Acute ICH - Meng-Die Wang; Yong Wang; Yuan-Peng Xia; Jing-Wen Dai; Lin Gao; Si-Qi Wang; Hai-Jun Wang; Ling Mao; Man Li; Shi-Meng Yu; Yan Tu; Quan-Wei He; et al. (Molecular Neurobiology, 2016)

Different Responses of an Invasive Clonal Plant Wedelia trilobata and its Native Congener to Gibberellin: Implications for Biological Invasion - Zhi-Cong Dai; Wei Fu; Shan-Shan Qi; De-Li Zhai; Si-Chong Chen; Ling-Yun Wan; Ping Huang; Dao-Lin Du (Journal of Chemical Ecology, 2016)

Differential effects of general anesthetics on anxiety-like behavior in formalin-induced pain: involvement of ERK activation in the anterior cingulate cortex - Cong Luo; Yan-Ling Zhang; Wei Luo; Fiona H Zhou; Chang-Qi Li; Jun-Mei Xu; Ru-Ping Dai (Psychopharmacology, 2015)

Comparison of SPE, IFE, and FLC in Monitoring Patients with Multiple Myeloma After Autologous Stem Cell Transplantation - Wei Li; Jia-Zi Zhou; Hui-Rong Chang; Li-Jun Dai; Zi-Ling Zhu; Yu-Feng Feng; Fei-Ran Gong; De-Pei Wu (Cell Biochemistry and Biophysics, 2015)

Upregulation of miR-197 inhibits cell proliferation by directly targeting IGFBP5 in human uterine leiomyoma cells - Jing Ling; Li Jiang; Chenxia Zhang; Jie Dai; Qunying Wu; Jie Tan (In Vitro Cellular & Developmental Biology - Animal, 2015)

Ion-exchange method in the collection of nitrate from freshwater ecosystems for nitrogen and oxygen isotope analysis: a review - Wen-Bing Li; Yao-Bin Song; Hong-Ke Xu; Ling-Yun Chen; Wen-Hong Dai; Ming Dong (Environmental Science and Pollution Research, 2015)

Analysis of Cancer Marker in Tissues with Hadamard Transform Fluorescence Spectral Microscopic Imaging - Hao Xu; Chuang Chen; Yue He; Hong-Wu Tang; Zhi-Ling Zhang; Yan Li; Dai-Wen Pang (Journal of Fluorescence, 2015)

Detection of inherited mutations for hereditary cancer using target enrichment and next generation sequencing - Yanfang Guan; Hong Hu; Yin Peng; Yuhua Gong; Yuting Yi; Libin Shao; Tengfei Liu; Gairui Li; Rongjiao Wang; Pingping Dai; Yves-Jean Bignon; Zhe Xiao; et al. (Familial Cancer, 2015)

Co-expression of the Arabidopsis SOS genes enhances salt tolerance in transgenic tall fescue (Festuca arundinacea Schreb.) - Dong-Mei Ma; Wei-Rong Xu; Hui-Wen Li; Feng-Xia Jin; Ling-Na Guo; Jing Wang; Hong-Jun Dai; Xing Xu (Protoplasma, 2014)

Genetic diversity and evolutionary characterization of Chinese porcine reproductive and respiratory syndrome viruses based on NSP2 and ORF5 - Jian-Kui Liu; Chun-Hua Wei; Xiao-Yan Yang; Xi-Lin Hou; AI-Ling Dai; Xiao-Hua Li; Mei-Kang Wei; Xiu-Zhen Pan (Archives of Virology, 2013)

Immunological effects of a 10-μg dose of domestic hepatitis B vaccine in adults - Jing-jing Ren; Xue-wei Dai; Zheng-gang Jiang; Ling-zhi Shen; Yong-di Chen; Qian Li; Wen Ren; Ying Liu; Jun Yao; Lan-juan Li (Journal of Zhejiang University-SCIENCE B, 2012)

Evaluation of seed storage protein gene 3′-untranslated regions in enhancing gene expression in transgenic rice seed - Wen Jing Li; Ling Ling Dai; Zhi Jian Chai; Zhi Jie Yin; Le Qing Qu (Transgenic Research, 2012)

Key parameter optimization and analysis of stochastic seismic inversion - Zhe-Yuan Huang; Li-Deng Gan; Xiao-Feng Dai; Ling-Gao Li; Jun Wang (Applied Geophysics, 2012)

Large-scale somatic embryogenesis and regeneration of Panax notoginseng - Xiang Ling You; Xiao Tan; Jin Ling Dai; Yu Hua Li; Yong Eui Choi (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Genetic evolution of equine influenza viruses isolated in China - Ting Qi; Wei Guo; Wen-Qiang Huang; Hong-Mei Li; Li-Ping Zhao; Ling-Li Dai; Na He; Xiao-Fang Hao; Wen-Hua Xiang (Archives of Virology, 2010)

Mitochondrial Dysfunction Induced by Statin Contributes to Endothelial Dysfunction in Patients with Coronary Artery Disease - Yuk-Ling Dai; Ting-Hin Luk; Chung-Wah Siu; Kai-Hang Yiu; Hiu-Ting Chan; Stephen W. L. Lee; Sheung-Wai Li; Sidney Tam; Bonnie Fong; Chu-Pak Lau; Hung-Fat Tse (Cardiovascular Toxicology, 2010)

Effects of Ginkgo biloba extracts on diazepam metabolism: a pharmacokinetic study in healthy Chinese male subjects - Xiao-Cong Zuo; Bi-Kui Zhang; Su-Jie Jia; Shi-Kun Liu; Ling-Yun Zhou; Jing Li; Jie Zhang; Ling-Ling Dai; Ben-Mei Chen; Guo-Ping Yang; Hong Yuan (European Journal of Clinical Pharmacology, 2010)

Groundwater discharge to the Changjiang River, China, during the drought season of 2006: effects of the extreme drought and the impoundment of the Three Gorges Dam - Zhi-jun Dai; Jin-zhou Du; Ao Chu; Jiu-fa Li; Ji-yu Chen; Xiao-ling Zhang (Hydrogeology Journal, 2010)

Bioenergetic Investigation of the Effects of La(III) and Ca(II) on the Metabolic Activity of Tetrahymena thermophila BF5 - Jie Dai; Chuan-Ling Li; Ye-Zhong Zhang; Qi Xiao; Ke-Lin Lei; Yi Liu (Biological Trace Element Research, 2008)

High-Level Secretion of a Chimeric Thermostable Lichenase from Bacillus subtilis by Screening of Site-Mutated Signal Peptides with Structural Alterations - Ling-lin Fu; Zi-rong Xu; Jiang-bing Shuai; Chun-xia Hu; Wei Dai; Wei-fen Li (Current Microbiology, 2008)

Persistence and dissipation of synthetic pyrethroid pesticides in red soils from the Yangtze River Delta area - Xiao-zhi Gu; Gang-ya Zhang; Li Chen; Rong-ling Dai; Yuan-chun Yu (Environmental Geochemistry and Health, 2008)